Hybrid APC in Combination With Resection for the Endoscopic Treatment of Neoplastic Barrett's Esophagus: A Prospective, Multicenter Study. (30th January 2022) - Knabe, Mate; Beyna, Torsten; Rösch, Thomas; Bergman, Jacques; Manner, Hendrik; May, Andrea; Schachschal, Guido; Neuhaus, Horst; Kandler, Jennis; Weusten, Bas; Pech, Oliver; Faiss, Siegbert; et al.
Abstract : INTRODUCTION: The current therapy of neoplastic Barrett's esophagus (BE) consists of endoscopic resection plus ablation, with radiofrequency ablation as the best studied technique. This prospective trial assesses a potential alternative, namely hybrid argon plasma ablation. METHODS: Consecutive patients with neoplastic BE undergoing ablation after curative endoscopic resection (89.6%) or primarily were included into this prospective trial in 9 European centers. Up to 5 ablation sessions were allowed for complete eradication of BE (initial complete eradication of intestinal metaplasia [CE-IM]), by definition including BE-associated neoplasia, documented by 1 negative endoscopy with biopsies. The main outcome was the rate of initial CE-IM in intention-to-treat (ITT) and per-protocol (PP) samples at 2 years. The secondary end points were the rate of recurrence-free cases (sustained CE-IM) documented by negative follow-up endoscopies with biopsies and immediate/delayed adverse events. RESULTS: One hundred fifty-four patients (133 men and 21 women, mean age 64 years) received a mean of 1.2 resection and 2.7 ablation sessions (range 1–5). Initial CE-IM was achieved in 87.2% of 148 cases in the PP analysis (ITT 88.4%); initial BE-associated neoplasia was 98.0%. On 2-year follow-up of the 129 successfully treated cases, 70.8% (PP) or 65.9% (ITT) showed sustained CE-IM; recurrences were mostly endoscopy-negative biopsy-proven BE epithelium and neoplasia in 3 cases. Adverse events were seen in 6.1%. DISCUSSION: Eradication and recurrence rates of Barrett's intestinal metaplasia and neoplasia by means of hybrid argon plasma coagulation at 2 years seem to be within expected ranges. Final evidence in comparison to radiofrequency ablation can only be provided by a randomized comparative trial.